Philosophy Embracing Humanities - Moutsopoulos, Yevangelos (Տիգրան Մեծ)
This paper discusses the following points of the history of philosophy and modern life. The emergence of philosophy – the longing for wisdom – in Ancient Greece as the historical point of formation of human rational reasoning. The formation of the ideal of kalokagathia – the art of fine speeches – as the main factor that initiated studia humaniora in Roman culture and the tradition of humanities in present days. The Greek language and literature as carriers of wisdom of Antic world that gave birth to Neoplatonism and Christian philosophy and mysticism. The rehabilitation of Aristotle’s Organon as the way to Neohellenic philosophy and the advent of the European Renaissance. Greek philosophy becoming an inseparable part of humanities in modern times. The unprecedented growth of technologies and globalization pushing aside philosophy and humanities in the interest of profit and immense wealth. The paradigm of corruption as the cause of worldwide detriment of individuals. Humanities and philosophy as the only warrants of an effective transition towards sane societies.
Keywords: Philosophy